THE MATHEMATICS USED IN THE HUMANITIES, SOCIAL SCIENCE, AND NATURAL SCIENCE AREAS IN A PROGRAM OF GENERAL EDUCATION OF THE COLLEGE LEVEL. - Leonhardy, Adele (Science Education, 1952)
The article presents a study on the mathematics used in the humanities, social science, and natural science areas in a program of general education at the University of Missouri in 1950. Mathematics is used extensively in each of the areas of general education. Physical science has the highest mathematical content per page, with biological science, the humanities, and social science following in order. The combined data for the textbook material show that approximately three-fourths of the mathematics used is quantitative, one-fifth is the mathematics of spatial relationships, and one-twentieth deals with logical structure. Lists of essential mathematics concepts and processes were determined for each of the areas and for the combined areas. The mathematics required for general education is relatively simple, for it is the arithmetic of the elementary school and certain processes from each of the four years of high school mathematics.